2020
DOI: 10.5152/eurasianjmed.2020.19224
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar Erector Spinae Plane Block as a Main Anesthetic Method for Hip Surgery in High Risk Elderly Patients: Initial Experience with a Magnetic Resonance Imaging

Abstract: Aims and Scope Eurasian Journal of Medicine (Eurasian J Med) is an international, scientific, open access periodical published by independent, unbiased, and triple-blinded peer-review principles. The journal is the official publication of Atatürk University School of Medicine and published triannually in February, June, and October. The publication language of the journal is English. The aim of the Eurasian Journal of Medicine is to publish original research papers of the highest scientific and clinical value … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 26 publications
2
55
0
1
Order By: Relevance
“…Comparison between the two studied groups according to atropine dose (mg). desflurane and reported the case had the same quality and duration to what they experienced by patients underwent the most common anaesthetic technique performed there (general anaesthesia and epidural analgesia) [31]. For controlled haemodynamics, we used B-blocker propranolol to control any incompatible rise of the heart rate.…”
Section: Case Nomentioning
confidence: 97%
“…Comparison between the two studied groups according to atropine dose (mg). desflurane and reported the case had the same quality and duration to what they experienced by patients underwent the most common anaesthetic technique performed there (general anaesthesia and epidural analgesia) [31]. For controlled haemodynamics, we used B-blocker propranolol to control any incompatible rise of the heart rate.…”
Section: Case Nomentioning
confidence: 97%
“…All surgeries were completed under mild propofol sedation. 72 It has been shown that in areas with complex innervation such as the hip and proximal femur, lumbar ESPB can be used as the main anesthetic method as it provides adequate anesthesia. The mechanism of action can be explained by the spread of LA given in lumbar EPSB to the paravertebral, epidural, and lumbar plexus.…”
Section: Main Anesthetic Methodsmentioning
confidence: 99%
“…The lumbar ESPB has been described for gender reassignment procedures, vaginismus and abdominal surgeries [ 1 , 2 ]. Also, recently, lumbar ESPB has been used successfully as the main anesthetic method for hip surgery [ 3 ]. An examination of the anatomy of the erector spinae muscle group reveals that it extends from the cervical to the sacral region; therefore, at least theoretically, ESPB can be performed at different levels along this entire vertebral column [ 4 ].…”
Section: Introductionmentioning
confidence: 99%